2014
DOI: 10.1159/000366375
|View full text |Cite
|
Sign up to set email alerts
|

Electric Stimulation at 448 kHz Promotes Proliferation of Human Mesenchymal Stem Cells

Abstract: Background/Aims: Capacitive-resistive electric transfer (CRET) is a non invasive electrothermal therapy that applies electric currents within the 400 kHz - 450 kHz frequency range to the treatment of musculoskeletal lesions. Evidence exists that electric currents and electric or magnetic fields can influence proliferative and/or differentiating processes involved in tissue regeneration. This work investigates proliferative responses potentially underlying CRET effects on tissue repair. Methods: XTT assay, flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
116
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 50 publications
13
116
1
1
Order By: Relevance
“…Note that, the proliferation rate is higher when the applied voltage is higher. Their findings agree with what prior works have suggested that electrical stimulation may induce cell proliferation or even differentiation 27, 28, 29. The proposed multifunctional pipette could have a potential use as a highly localized single cell electrical stimulator for biological studies and other applications, in addition to examples demonstrated in the current work.…”
Section: Resultssupporting
confidence: 92%
“…Note that, the proliferation rate is higher when the applied voltage is higher. Their findings agree with what prior works have suggested that electrical stimulation may induce cell proliferation or even differentiation 27, 28, 29. The proposed multifunctional pipette could have a potential use as a highly localized single cell electrical stimulator for biological studies and other applications, in addition to examples demonstrated in the current work.…”
Section: Resultssupporting
confidence: 92%
“…Electric fields (EFs) can regulate a variety of cell functions, including growth, adhesion, reorganization of cytoskeleton, contractility, differentiation, proliferation, activation of intracellular pathways, secretion of proteins and gene expression [1][2][3][4][5][6][7]. The regulatory effect of EFs has been demonstrated on different cell types such as neurons, osteoblasts, myoblasts, fibroblasts, endothelial cells, muscle cell and epithelial cells [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, bone marrow procurement causes considerable discomfort to the patient and yields a relatively small number of harvested cells. More recent animal and clinical studies have shown that adipose-derived stem cells (ASCs) are capable of repairing damaged soft tissue, bone or cartilage defects [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%